Review and prospect on the research of dynamic spectrum sharing - Yan FENG; Hao SUN; Ying XU; Jian FANG (Dianxin kexue)
As one of the most efficient ways to alleviate the problem of spectrum scarcity，dynamic spectrum sharing has drawn worldwide attention. Firstly，the concept of dynamic spectrum sharing was briefly introduced. Next，from the aspects of rulemaking，standardization and application，the international development of dynamic spectrum sharing was fully investigated. Finally，based on the current situation of radio management，the impact and challenges on frequency management，radio station management and radio monitoring were analyzed.